METAQU; A STRATEGI TO ENHANCE READING QUR'AN CAPABILITY THROUGH WALI ASUH - Roisyah, Hannani; Hambali, Hambali; Rahman, Fathor (Nurul Jadid University, Paiton Probolinggo, East Java, 2022)
This study aims to determine the improvement of students' ability to read the Qur'an through the talqin method. The method used is a qualitative approach with the type of case study, Data collection techniques using observation, interviews, and documentation. While the data analysis uses the air flow model which consists of three stages, namely: reducing data, presenting data, then drawing conclusions/verification. The results showed that the talqin method is an appropriate learning method in increasing the students' ability to read the Qur'an, and the talqin method is very influential on the improvement of the students' ability to read the Qur'an. This study implies that the talqin method can facilitate students in learning to read the Qur'an, especially in increasing the ability to read the Qur'an of students.